Symbolic Meaning of Drama “Perlawanan Diponegoro” - Sahid, Nur; Susantina, Sukatmi; Septiawan, Nicko (Harmonia: Journal of Arts Research and Education, 2016)
Study on Drama entitled “Perlawanan Diponegoro” or “Diponegoro Insurrection” by Lephen Purwanto is aiming at deeply digging the semiotic meanings attached to it. This study employed Keir Elam’s theatrical semiotics as the approach, while Krippendorf’s content analysis was implemented as the method of study. Citing from Krippendorf, content analysis is a method that is particularly develop to study symbolical phenomena with a major purpose that is to dig and reveal other examined phenomena, comprising content, meaning, and essential element of a literary work.